Handbook of current and novel protocols for the treatment of infertility - Dahan, Michael H. (Academic Press, 2023)
The field of Assisted Reproductive Technology (ART) is rapidly evolving and stimulation protocols, fertility strategies and aspects of infertility treatments are constantly being updated as advances and new discoveries are made. Handbook of Current and Novel Protocols for the Treatment of Infertility is a valuable resource of well-organized, comprehensive scientific data with practical guides and step-by-step protocols for infertility management. Written by world-wide experts, this book discusses different practice patterns and approaches used internationally and presents innovative topics including preimplantation genetic testing, time lapse imaging and the role of artificial intelligence in ART. This book provides up-to-date, evidence-based guidance on daily practice and is an important resource for infertility providers, including trainees or experienced clinicians, embryologist, and is geared for both specialist in reproductive medicine and gynecologists interested in increasing their knowledge in the field of reproductive endocrinology and intertility.